The viability of Virtual Reality in Finnish upper secondary school - Niittymäki, Niki (My University, 2021)
The effects of Virtual Reality in the educational context have been covered to some extent, but it has resulted in mixed findings. The use of VR solutions as an additional educational tool has shown promising positive impacts on the learning experience. Such research has been conducted mostly as short sessions in isolated lab environments, which are optimal for VR, but not indicative of actual learning environments. The lack of real-world data warrants more research. Thus, this research analyses the potential of an affordable VR solution as an educational tool in a real Finnish upper secondary school classroom, by measuring the performance of the students and how they react to the use of the proposed solution. To evaluate the viability of a realistic VR solution, the students were given mobile clip-on VR lenses that utilize their personal smartphones. The research was conducted during three classes, that were a part of an actual Biology introduction course. The students were surveyed before, during and after the research. In conclusion, the study shows that the proposed VR solution could be used as an educational tool. Additionally, features that future work related to educational VR solutions should consider are recommended.
Keywords: Virtual Reality, Education, Educational tool, Finnish Upper Secondary School